Basic Pharmacokinetic Concepts and Some Clinical Applications - A Ahmed, Tarek (IntechOpen, 2015)
This book considers the basic principles of biopharmaceutics and pharmacokinetics. It also illustrates clinical pharmacokinetic applications, such as recirculatory models, common antimalarial drugs, and clinical pharmacokinetic principles in critically ill patients, which are essential for medical professionals. Undergraduate and postgraduate students can make use of the information presented. The contents of the book represent the authors points of view as well as clinical findings and basic concepts of pharmacokinetics and biopharmaceutics that are covered in textbooks.